Cetuximab promotes RSL3-induced ferroptosis by suppressing the Nrf2/HO-1 signalling pathway in KRAS mutant colorectal cancer - Jiawen Yang (Nature Publishing Group, 2021)
Abstract Cetuximab is approved for the treatment of metastatic colorectal cancer (mCRC) with RAS wild-type. Nevertheless, the prognosis remains poor and the effectiveness of cetuximab is limited in KRAS mutant mCRC. Recently, emerging evidence has shown that ferroptosis, a newly discovered form of nonapoptotic cell death, is closely related to KRAS mutant cells. Here, we further investigated whether cetuximab-mediated regulation of p38/Nrf2/HO-1 promotes RSL3-induced ferroptosis and plays a pivotal role in overcoming drug resistance in KRAS mutant colorectal cancer (CRC). In our research, we used two KRAS mutant CRC cell lines, HCT116 and DLD-1, as models of intrinsic resistance to cetuximab. The viability of cells treated with the combination of RSL3 and cetuximab was assessed by the CCK-8 and colony formation assays. The effective of cetuximab to promote RSL3-induced ferroptosis was investigated by evaluating lipid reactive oxygen species accumulation and the expression of the malondialdehyde and the intracellular iron assay. Cetuximab therapy contributed to regulating the p38/Nrf2/HO-1 axis, as determined by western blotting and transfection with small interfering RNAs. Cetuximab promoted RSL3-induced ferroptosis by inhibiting the Nrf2/HO-1 in KRAS mutant CRC cells, and this was further demonstrated in a xenograft nude mouse model. Our work reveals that cetuximab enhances the cytotoxic effect of RSL3 on KRAS mutant CRC cells and that cetuximab enhances RSL3-induced ferroptosis by inhibiting the Nrf2/HO-1 axis through the activation of p38 MAPK.